Effect of Dipeptides on In vitro Maturation, Fertilization and Subsequent Embryonic Development of Porcine Oocytes - Tareq, K. M. A. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
The effects of amino acids and dipeptides on in vitro production of porcine embryos and accumulation of ammonia in culture medium during developmental stages were examined in this study. The maturation, fertilization and development of embryonic cultures were performed in modified Tissue culture medium (mTCM)-199 supplemented with 10% (v/v) porcine follicular fluid, modified Tyrode’s albumin lactate pyruvate (mTALP) medium, and modified North Carolina State University (mNCSU)-23 medium, respectively. In addition, amino acids and dipeptides of different concentrations and combinations were used to treat the embryos. The addition of L-alanyl-L-glutamine (AlnGln)+L-glycyl-L-glutamine (GlyGln) significantly (p<0.05) improved oocyte maturation, fertilization and the incorporation and oxidation of (14)C(U)-glucose when compared to the control group and other treatment groups. Additionally, 2–4 cell, 8–16 cell, morula and blastocyst development increased significantly (p<0.05) following treatment with AlnGln+GlyGln when compared to the control group and other treatment groups, while this treatment reduced the accumulation of ammonia. Taken together, these findings suggest that treatment with AlnGln+GlyGln may play an important role in increasing the rate of porcine oocyte maturation, fertilization and embryonic development by reducing the level of accumulated ammonia measured in the culture media.